An integrated CRITIC and MABAC based type-2 neutrosophic model for public transportation pricing system selection. (March 2022) - Simic, Vladimir; Gokasar, Ilgin; Deveci, Muhammet; Karakurt, Ahmet
Abstract: The pricing of public transportation services is a complex task that authorities deal with because many criteria should be considered while deciding on the pricing system. Some include decentralization of the cities due to lower rents in outer-city regions and operating costs of longer transportation lines. Hence, four alternative public transportation pricing systems are defined, which are flat fare, distance-based, zonal, and rent-based fare. To prioritize these alternatives, four aspects are determined, namely cost, transportation, social and political, and there are 13 criteria present under these aspects. A two-stage hybrid multi-criteria decision-making model based on type-2 neutrosophic numbers (T2NNs) is introduced to provide a straightforward and flexible decision-making tool for researchers and practitioners. In its first stage, the reputation of the experts is determined under the T2NN environment. Second, the novel T2NN-based CRiteria Importance Through Intercriteria Correlation (CRITIC) method is employed to evaluate the criteria importance, while the new T2NN-based Multi-Attributive Border Approximation area Comparison (MABAC) method is used to rank the public transportation pricing systems. The results show that rent-based fare pricing is the most advantageous alternative. The high reliability and robustness of the integrated CRITIC and MABAC based type-2 neutrosophic model are demonstrated with the comparative and sensitivity analyses. Highlights: Public transportation pricing system selection problem is addressed and solved. Practical and methodological frameworks for public transportation pricing are given. Integrated CRITIC and MABAC based type-2 neutrosophic model is introduced. The presented hybrid T2NN-based model is highly robust, reliable, and flexible. The most advantageous pricing system is the rent-based fare.